2017
DOI: 10.1177/0300060516686873
|View full text |Cite
|
Sign up to set email alerts
|

Subtotal resection of vestibular schwannoma: Evaluation with Ki-67 measurement, magnetic resonance imaging, and long-term observation

Abstract: PurposeThe aim of this study was to compare the postoperative clinical and radiological data of patients with vestibular schwannomas who were initially managed by near total resection (NTR) or subtotal resection (STR). The Ki-67 analysis results were compared with tumor regrowth to determine the presence of a correlation between this proliferative index and postoperative tumor regrowth.Study DesignSeventeen adult patients (7 male, 10 female) were retrospectively reviewed. Nine (52.9%) and eight (47.1%) patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…However, in a case series with 15 clinically aggressive vestibular schwannomas that all showed a radiological growth rate of > 15 mm/year, MIB1 expression was significantly increased compared to a control group [14]. It has also been described that the risk of regrowth after VS resection is associated with an increased MIB1 expression [9, 15].…”
Section: Discussionmentioning
confidence: 99%
“…However, in a case series with 15 clinically aggressive vestibular schwannomas that all showed a radiological growth rate of > 15 mm/year, MIB1 expression was significantly increased compared to a control group [14]. It has also been described that the risk of regrowth after VS resection is associated with an increased MIB1 expression [9, 15].…”
Section: Discussionmentioning
confidence: 99%
“…The MIB-1 index was not significantly correlated with regrowth or recurrence despite our finding that the mean value of the MIB-1 index was slightly higher in the cases with recurrence. In the literature, the MIB-1 index has been associated with recurrence [22,46]. A retrospective study of 17 patients by Iannella et al [22] claimed that a MIB-1 index > 2.5% is a predictor of tumour regrowth and that these patients should be carefully monitored by radiological follow-up.…”
Section: Mib-1 Proliferation Indexmentioning
confidence: 99%
“…In the literature, the MIB-1 index has been associated with recurrence [22,46]. A retrospective study of 17 patients by Iannella et al [22] claimed that a MIB-1 index > 2.5% is a predictor of tumour regrowth and that these patients should be carefully monitored by radiological follow-up. Strong evidence for a significant association between the MIB-1 index and tumour recurrence in vestibular schwannoma is provided in the study by Panigrahi et al [32] which investigated 144 patients who underwent surgical excision for sporadic vestibular schwannoma.…”
Section: Mib-1 Proliferation Indexmentioning
confidence: 99%
“…Therefore, it is important to understand the behavior of residual tumors following an incomplete resection. Some authors showed that small, devascularized residual tumors do not grow 18 20 , while others proved that the proliferative activity of the tumor itself contributes to regrowth 21 23 . The question of whether the residual tumor will grow or not will depend on the pattern of regrowth, in which the incidence and rate of regrowth, and the benefit on neurological outcome need to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors including EOR 16 , 17 , 28 , residual tumor volume 17 , 25 , 27 , 34 36 , and the proliferative activity of the tumor itself 21 23 have been reported to contribute to regrowth after incomplete resection of VS, but still, little is known about the significant clinicopathological factors 24 , 26 , 29 33 . In this study, an immediate postoperative tumor volume ≥ 0.7 cm 3 had almost an 11-fold greater risk and residual tumor location other than IAC had a sixfold greater risk of a regrowth than tumors that were less than 0.7 cm 3 or in IAC.…”
Section: Discussionmentioning
confidence: 99%